Salmeterol in paediatric asthma. Issue 9 (1st September 2000) - Byrnes, Catherine; Shrewsbury, Stephen; Barnes, Peter J; Bush, Andrew
Abstract : BACKGROUND: The addition of long acting inhaled β2 agonists is recommended at step 3 of the British guidelines on asthma management but a recent study suggested no additional benefit in children with asthma. METHODS: The aim of this study was to compare, in a double blind, three way, crossover study, the effects of the addition of salmeterol 50 μg bd, salmeterol 100 μg bd, and salbutamol 200 μg qds in asthmatic children who were symptomatic despite treatment with inhaled corticosteroids in a dose of at least 400 μg/day over a one month period. Symptom scores, morning and evening peak expiratory flow (PEF) rates, use of rescue medication, spirometric indices, and histamine challenge were measured. RESULTS: Forty five children aged 5–14 years were enrolled. All three treatments improved asthma control, morning and evening PEF rates, and spirometric indices with no change in bronchial hyperreactivity. Mean morning PEF was significantly better during the salmeterol treatment periods than with salbutamol treatment (p<0.05). The analysis of mean morning PEF gave an estimated treatment difference of 9.6 l/min for salmeterol 50 μg bd versus salbutamol 200 μg qds (95% confidence interval (CI) 2.1 to 17.1), and an estimated treatment difference of 13.8 l/min for salmeterol 100 μg bd versus salbutamol 200 μg qds (95% CI 6.0 to 21.5). There were no significant differences between the two doses of salmeterol and all treatments were well tolerated. CONCLUSIONS: In this population of moderate to severe asthmatic children on inhaled corticosteroids, salmeterol in a dose of either 50 μg bd or 100 μg bd is significantly more effective at increasing the morning PEF rate over a one month period than salbutamol 200 μg qds. The data provided no significant evidence of a difference in efficacy between the two doses of salmeterol, 50 μg and 100 μg. A trial of salmeterol 100 μg bd may be worth considering in those still symptomatic on the lower dose.